Un/Known bodies: dissecting Sara Baartman in the Francophone autobiography, 53cm (Bessora, 1999). Issue 2 (4th May 2017) - Moji, Polo B.
ABSTRACT: The dissection of Sarah Baartman's body is considered a colonial scientific practice that rendered the Africans "less than human." This paper is interested in how this project travels into Francophone literature through the autobiographical novel 53cm (1999) by Swiss–Gabonese author Sandrine Bessora van Nguema. Dedicated to Baartman, 53cm depicts Bessora's alter-ego, Zara, an illegal alien in Paris. Although skinny-bottomed Zara is the embodied opposite of Baartman's steatopygia, she too is considered "alien" by French society. I analyse Zara's lived experience as a "known" body who is subject to a dissecting gaze based in the anatomical "knowledge" of Sarah's enlarged buttocks. Conversely, I consider dissection as a subversive practice in Zara's satirical performance of being an ethnographer of French (the "knower"). I conclude that the Zara/Sarah representational model reframes dissection as a subversive performance born of the feeling of indignity created by persistent colonial ontological categories.